GRAIN GROWTH KINETICS OF CaIrO3 PEROVSKITE AND POST-PEROVSKITE, WITH IMPLICATIONS FOR RHEOLOGY OF D″ LAYER - Yoshino T.; Yamazaki D. (My University, 2007)
Grain growth kinetics of CaIrO3 perovskite and post-perovskite aggregates was investigated by time-series experiments at pressures of 2 and 3 GPa and temperatures ranging from 1373 to 1773 K in a piston cylinder apparatus. The experiments were conducted in the stability field of both perovskite and post-perovskite. The increase of grain size (G) with time (t) follows a growth law: Gn-G0n = k · t (k = k0 exp(- H*/RT)). The growth exponents (n) for perovskite and post-perovskite are 2.6 ± 0.5 and 4.5 ± 0.9, respectively. The activation enthalpy (H*) of post-perovskite grain growth is 251 ± 35 kJ/mol. Grain growth of post-perovskite is distinctly slower than that of perovskite. Sluggish grain growth of the post-perovskite is caused by its strong anisotropic shape. The phase transition from the perovskite to the post-perovskite at the D" discontinuity would lead to maintenance of small grain size in the D" layer. If diffusion creep is the dominant deformation mechanism of post-perovskite, the phase transformation would induce the significant softening of the D" layer due to slow growth rate of post-perovskite compared with a situation without the phase transition. © 2007 Elsevier B.V. All rights reserved.
Keywords: D″ LAYER; DIFFUSION CREEP; GRAIN GROWTH; POST-PEROVSKITE; PROVSKITE; RHEOLOGY